Cyanoacrylate Granuloma After Cyanoacrylate Closure of Incompetent Saphenous Veins. Issue 10 (3rd October 2021) - Sermsathanasawadi, Nuttawut; Pruekprasert, Kanin; Chinsakchai, Khamin; Wongwanit, Chumpol; Ruangsetakit, Chanean
Abstract : BACKGROUND: Cyanoacrylate closure (CAC) is a minimally invasive surgery to treat incompetent saphenous veins. OBJECTIVE: To evaluate the incidence, the risk factors for, and the management of cyanoacrylate granuloma (CAG) after CAC of incompetent saphenous veins in patients with chronic venous disease. MATERIALS AND METHODS: Data specific to incompetent saphenous veins, including great saphenous veins, anterior accessory saphenous veins, and small saphenous veins, that were treated with CAC were retrospectively evaluated. RESULTS: A total of 126 saphenous veins from 101 patients were included. Recapture of the delivery catheter before withdrawal was not performed in all patients. Cyanoacrylate granuloma occurred in 3 of 101 (2.9%) patients, and in 3 of 126 (2.3%) treated saphenous veins. All patients with CAG presented with granuloma and abscess at the puncture site 3 to 5 months after CAC. All patients were treated with incision, drainage, and removal of the glue foreign body. No recurrent granuloma was observed during the study period. No patient or procedural predictive factor for CAG was identified. CONCLUSION: Cyanoacrylate granuloma is not a rare complication after CAC when recapture of the delivery catheter is not performed. Patients should be advised of the possibility of CAG after CAC.